Implementação de Arquitetura IIoT para virtualização de controle utilizando CLP S7-1200 e Gateway IOT2050 - Lino, Ícaro Luiz de Souza (2025)
Industry 4.0 represents a revolution in industrial production, characterized by the digitization and integration of physical and digital systems, using technologies such as IIoT and Artificial Intelligence. With the advent of Cyber-Physical Systems, the possibility arises of virtualizing industrial process control logic, optimizing production processes in real time and increasing operational flexibility. This paper presents the implementation of an architecture comprising a Siemens S7-1200 PLC, an IoT2050 gateway and an application running on a remote server. To make it possible to transfer the control logic of an industrial process to the remote server, methods such as collecting timestamps and analyzing delay times in different scenarios were used. The IoT2050 Gateway was configured to act as an intermediary between the process controller and the server, using protocols such as MQTT and S7. In the tests carried out, the average Round-Trip Delay (RTD) in the initial scenario was 30.73 ms, while in the third scenario, with the virtualized control logic, there was an increase to 45.51 ms. The results demonstrate the system’s potential for industrial applications in environments where the controllers and gateways are connected via local networks, even if the remote server is physically distant.